Efektivitas Pengomposan Pupuk Organik dari Kotoran Kambing dan Jerami Padi Menggunakan Bioaktivator Orgadec - Jesvica, Jesvica; Dona, Afrini; Migusnawati, Migusnawati; Komala, Refika (UNIVERSITAS LABUHANBATU, 2024)
Careless disposal of livestock manure can lead to environmental pollution, thereby impacting the deterioration of the quality of the environment, the quality of life of the rancher and his livestock and triggering social conflicts. So this needs to be addressed by making livestock waste as compost fertilizer. This study aims to determine whether organadec bioactivators are effective against composting manure from goat manure and rice straw. The study was conducted during a 21-day observation period of goat manure and rice straw so that it became compost fertilizer. This study used an experimental method with 4 treatments and 4 repeat doses of organadec bioactivator against measurements of fertilizer levels consisting of Water Content, Nitrogen (N), Phosphorus (P), and Potassium (K). The results of the study showed that administration of orgadec gave results that did not differ markedly with respect to Water Content and Nitrogen content. But it differs markedly in the content of Phosphorus and Potassium. It can be concluded that organadec bioactivators can increase the nutrient content, namely the content of Moisture, Nitrogen, Phosphorus and Potassium contained in composted organic fertilizers. Keywords: compost, orgadec, manure, goat, straw